Pengaruh Digital Marketing, Influencer Marketing Dan Product Quality Terhadap Keputusan Pembelian Mobil Wuling Di Indonesia: Digital Marketing, Product Quality, Keputusan pembelian - Baronah; Anggit Yoebrilianti; Nurhayani (Jurnal Akuntansi Manajemen (JAKMEN), 2023)
Consumer behavior in Indonesia in making car purchase decisions is influenced by many factors some of which are digital Marketing, Influencer Marketing and Product Quality, this also includes the purchase of Wuling Motors brand cars. The method used is a quantitative approach that examines specific populations and samples. Data collection using research instruments and data analysis is quantitative / statistical. The purpose of this study is to test the hypothesis that has been set. Data processing using the help of the SPSS program. The result of the study is that Digital Marketing has a negative and significant influence on purchasing decisions. Digital Marketing, Influencer Marketing, Product Quality simply have an influence on purchasing decisions.